Estudo anatômico da enxertia em Citrus spp. - Shimoya, C; J Gomide, C; Maurício Fortes , José (Revista Ceres, 2025)
Anatomical studies of bud grafting of Citrus limon (L.) Burn. on Citrus sinensis (L.) Osbeck during the taking phase have shown the following pattern of events.